Liberdade em clausura: Trajetórias pessoais e religiosas de monjas carmelitas descalças - Garcia, Miriam Verri (2006)
The main focus of this essay is religious women living in cloisters trying to identify the reasons why they have chosen this type of life. Based on the premises that these women freely decide to live in cloisters, a deep analysis of the social context and the role they play in this context is done. Through these women s lives we can observe certain elements that may indicate the reasons for their choices. The research work was developed in Ordem das Carmelitas Descalças monastery in São Paulo s countryside aiming at finding records about the essay s subject. Through the life report of five lady monks plus a questionnaire focusing on indications of the social-economic level of the monastery population it was possible to better understand the life style of the monastery. The results seem to indicate important reasons related to their family biodata, as well as a possible lack of life perspectives of these women as fundamental elements of their choices. Besides that the essay leads to the need of further investigation focusing on different aspects of life in cloisters and its relationship with society